China's belt and road initiative in Portuguese speaking countries: Portuguese and Angolan perspectives - Zhang Jinming (2019)
The rapid economic growth in China has always been one of the most controversial issues in the world economy, where the role of the Belt and Road Initiative has been highlighted as strategic. This study aims at knowing and analyzing the implementation and motivation of China’s Belt and Road Initiative (BRI) strategy in Portuguese speaking countries, with Portuguese and Angolan perspectives. The focus of this research is to understand the mutual motivations and interests between China and Portuguese speaking countries (Comunidade dos Países de Língua Portuguesa, CPLP in short) in the BRI. It is further aimed at examining the BRI impact on China-Portuguese speaking countries relations and exploring whether a win-win cooperation in these countries. This study used both a second hand data from existing publication and database and first hand data collected through interviews of five Portuguese and five Angolan. The key findings study suggests the followings. First of all, BRI as a global strategy of China is both market-driven and resource-driven. Second, BRI not only plays a vital role in China’s integration into the global economy, but also help boosting both economic and social development between China and Portuguese-speaking countries in the BRI framework. Lastly, although BRI so far leads to win-win results in Portugal and Angola, it’s difficult to judge the long-term effects.